Synthesis and evaluation of diethylethylamine-chitosan for gene delivery: Composition effects on the in vitro transfection efficiency - De Paula Pansani Oliveira, Franciele [UNESP]; Picola, Isadora Pfeifer Dalla [UNESP]; Shi, Qin; Barbosa, Hellen Franciane Gonçalves [UNESP]; De Oliveira Tiera, Vera Aparecida [UNESP]; Fernandes, Júlio Cesar; Tiera, Marcio José [UNESP] (IOP Publishing, 2013)
Chitosan has been indicated as a safe and promising polycation vector for gene delivery. However its low transfection efficiency has been a challenging obstacle for its application. To address this limitation, we synthesized chitosan derivatives which had increasing amounts of diethylethylamine groups (DEAE) attached to the chitosan main chain. The plasmid DNA VR1412 (pDNA), encoding the ß-galactosidase (ß-gal) reporter gene was used to prepare nanoparticles with the chitosan derivatives, and the transfection studies were performed with HeLa cells. By means of dynamic light scattering and zeta potential measurements, it was shown that diethylethylamine-chitosan derivatives (DEAEx-CH) were able to condense DNA into small particles having a surface charge depending on the polymer/DNA ratio (N/P ratio). Nanoparticles prepared with derivatives containing 15 and 25% of DEAE groups (DEAE15-CH and DEAE25-CH) exhibited transfection efficiencies ten times higher than that observed with deacetylated chitosan (CH). For derivatives with higher degrees of substitution (DS), transfection efficiency decreased. The most effective carriers showed low cytotoxicity and good transfection activities at low charge ratios (N/P). Vectors with low DS were easily degraded in the presence of lysozyme at physiological conditions in vitro and the nontoxicity displayed by these vectors opens up new opportunities in the design of DEAE-chitosan-based nanoparticles for gene delivery. © 2013 IOP Publishing Ltd.
Keywords: Charge ratio; Chitosan derivatives; Deacetylated chitosans; Degrees of substitution; Galactosidases; Gene Delivery; HeLa cell; In-vitro; Main chains; Non-toxicity; Physiological condition; Plasmid DNA; Polycations; Reporter gene; Small particles; Transfection activity; Transfection efficiency; Zeta potential measurements; Efficiency; Gene encoding; Gene transfer; Nanoparticles; Zeta potential; Chitosan